Detection of hidden faults within the Fucino basin from single-station ambient noise measurements: The case study of the Trasacco fault system - Famiani, Daniela; Cara, Fabrizio; Di Giulio, Giuseppe; Vassallo, Maurizio; Milana, Giuliano (Frontiers in Earth Science, 2022)
The presence of normal fault systems in central Italy, outcropping or hidden below Quaternary covers in intra-mountain basins, is the expression of the Neogene–Quaternary evolution of the area, characterized by an extensional tectonic regime following the fold and thrust structuring of the Apennine orogen. Italian urban settlements of central Italy are developed on hills or mountains but also in lowland areas, which are often set up in sedimentary basins. In this framework, urban centers found close to fault lines are common, with strong implications on the seismic risk of the area. In this work, we performed a dense seismological passive survey (88 single-station ambient noise measurements) and used the horizontal-to-vertical spectral ratio (HVNSR) technique to investigate hidden faults in the Trasacco municipality located in the southern part of the Fucino Basin (central Italy), where microzonation studies pointed out hypothetical fault lines crossing the urban area with the Apennine orientation. These hidden structures were only suggested by previous studies based on commercial seismic lines and aerial photogrammetry; their presence in the basin area is confirmed by our measurements. This case study shows the potentiality of using the HVNSR technique in fault areas to have a preliminary indication of anomalous behaviors, to be investigated later with specific geophysical techniques. Our approach can support microzonation studies whenever fault zones are involved, especially in urban areas or in places designated for future developments.